Mesenchymal stem cells engineered to express selectin ligands and IL-10 exert enhanced therapeutic efficacy in murine experimental autoimmune encephalomyelitis. (January 2016) - Liao, Wenbin; Pham, Victor; Liu, Linan; Riazifar, Milad; Pone, Egest J.; Zhang, Shirley Xian; Ma, Fengxia; Lu, Mengrou; Walsh, Craig M.; Zhao, Weian
Abstract: Systemic administration of mesenchymal stem cells (MSCs) affords the potential to ameliorate the symptoms of Multiple Sclerosis (MS) in both preclinical and clinical studies. However, the efficacy of MSC-based therapy for MS likely depends on the number of cells that home to inflamed tissues and on the controlled production of paracrine and immunomodulatory factors. Previously, we reported that engineered MSCs expressing P-selectin glycoprotein ligand-1 (PSGL-1) and Sialyl-Lewis x (SLeX) via mRNA transfection facilitated the targeted delivery of anti-inflammatory cytokine interleukin-10 (IL-10) to inflamed ear. Here, we evaluated whether targeted delivery of MSCs with triple PSGL1/SLeX/IL-10 engineering improves therapeutic outcomes in mouse experimental autoimmune encephalomyelitis (EAE), a murine model for human MS. We found PSGL-1/SLeX mRNA transfection significantly enhanced MSC homing to the inflamed spinal cord. This is consistent with results from in vitro flow chamber assays in which PSGL-1/SleX mRNA transfection significantly increased the percentage of rolling and adherent cells on activated brain microvascular endothelial cells, which mimic the inflamed endothelium of blood brain/spinal cord barrier in EAE. In addition, IL-10-transfected MSCs show significant inhibitory activity on the proliferation of CD4 + T lymphocytes from EAE mice. In vivo treatment with MSCs engineered with PSGL-1/SLeX/IL-10 in EAE mice exhibited a superior therapeutic function over native (unmodified) MSCs, evidenced by significantly improved myelination and decreased lymphocytes infiltration into the white matter of the spinal cord. Our strategy of targeted delivery of performance-enhanced MSCs could potentially be utilized to increase the effectiveness of MSC-based therapy for MS and other central nervous system (CNS) disorders.